2012
DOI: 10.4269/ajtmh.2012.11-0606
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Factors Present in Dengue Patient Sera Induces Alterations of Junctional Proteins in Human Endothelial Cells

Abstract: Abstract. Plasma leakage in severe dengue has been postulated to be associated with skewed cytokine immune responses. In this study, the association of cytokines with vascular permeability in dengue patients was investigated. Human serum samples collected from 48 persons (13 with dengue fever, 29 with dengue hemorrhagic fever, and 6 healthy) were subjected to cytokines analysis by using Luminex Multiplex Technology. Selected serum samples from patients with dengue hemorrhagic fever sera and recombinant human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 19 publications
1
43
0
4
Order By: Relevance
“…This evidence indicates that the epithelial barrier dysfunction observed as a reduction in TER is a consequence of circulating soluble factors present in the ADE-CM. Interestingly, a recent report suggests that cytokine factors present in serum samples collected from patients with SD induced morphological alterations in human umbilical vein endothelial cells (HUVECs) with perturbations in the ZO-1 and VE-cadherin proteins (63). Thus, a risk connection between the proinflammatory immune response of ADE-DENV-infected macrophages and the phenomenon of barrier dysfunction observed in patients with VPS can now be proposed.…”
Section: Figmentioning
confidence: 99%
“…This evidence indicates that the epithelial barrier dysfunction observed as a reduction in TER is a consequence of circulating soluble factors present in the ADE-CM. Interestingly, a recent report suggests that cytokine factors present in serum samples collected from patients with SD induced morphological alterations in human umbilical vein endothelial cells (HUVECs) with perturbations in the ZO-1 and VE-cadherin proteins (63). Thus, a risk connection between the proinflammatory immune response of ADE-DENV-infected macrophages and the phenomenon of barrier dysfunction observed in patients with VPS can now be proposed.…”
Section: Figmentioning
confidence: 99%
“…There is increasing evidence that the immune system plays a key role in determining the severity of dengue disease [18,19], in particular the array of cytokines produced during infection [8,9,10,24]. The role of T lymphocytes in this process is controversial since on the one hand there is evidence that activation of T lymphocytes leads to pro-inflammatory cytokine synthesis [20,21,22,23,24,25,26,27] and on the other there is evidence that T-lymphocyte proliferation in dengue patients is impaired [28,29,30,31] and that patients with acute DENV infection are leukopenic [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that lead to these clinical outcomes are unknown, however there is growing evidence that the pathophysiology of dengue is mediated by host immune response [2,4]. Several lines of evidence indicate that anti-dengue antibodies [5,6,7], cytokines [8,9,10], soluble immune mediators [11,12,13] and cross-reactive memory T lymphocytes [14,15,16], along with high dengue viral loads [17], contribute to the progression to DHF/DSS and death [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…14,17 The factors that cause vascular leak are thought to be present in serum of dengue patients, as sera from dengue patients have shown to reduce expression of gap junction proteins thus leading to vascular leak. 18 Among the potential mediators that cause vascular leak, VEGF has been extensively studied in dengue, 19,20 and it has been shown that free plasma VEGF levels are significantly higher and VEGF receptor 2 levels are significantly lower in those with DHF. 20 In addition, the rise in VEGF and fall in VEGFR2 was shown to correlate with the onset of vascular leak.…”
Section: Mediators That Cause Vascular Leakmentioning
confidence: 99%